Overview of Hypertension in the Elderly at the Health Center: A Descriptive Study - Nugroho, Ma'ruf Aji; Nurhidayati, Tri; Hidayati, Eni (South East Asia Nursing Research, 2024)
Hypertension is systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. An elderly person is over 60 years old. To find out the picture of hypertension in the elderly at the Kedungmundu Health Center. Design study is quantitative descriptive, and subjects are elderly with hypertension at the Kedungmundu Health Center, totaling 184. The variables hypertension in the elderly, with univariate analysis and questionnaire instruments. The research at the Kedungmundu Health Center in January-February 2024. Normal blood pressure was 59 (32.1%), and hypertension II was 36 (19.6%). There are 165 (89.7%) non-smoking and 9 (4.9%) smokers. There were 182 (98.9%) not consume alcohol and 2 (1.1%) consumed. There were 111 (60.3%) good physical activities, while 73 (39.7%) poor physical activities. Consuming good junk food was 102 (55.4%), while the bad was 82 (44.6%). There were 106 (57.6%) with a family history of non-communicable diseases, while no descendants with a family history of non-communicable diseases 78 (42.4%). The highest blood pressure is in the normal. Most people do not smoke. The majority do not consume alcohol. The most physical activity is in the good. Most of them consume junk food in the good. The majority have with a family history of non-communicable diseases. The Kedungmundu Health Center is expected to improve health services and hold Prolanis and gymnastics in each village to make it easier for the elderly to participate.